2009
DOI: 10.1112/jtopol/jtp015
|View full text |Cite
|
Sign up to set email alerts
|

Floer homology and singular knots

Abstract: Abstract. In this paper we define and investigate variants of the link Floer homology introduced by the first and third authors. More precisely, we define Floer homology theories for oriented, singular knots in S 3 and show that one of these theories can be calculated combinatorially for planar singular knots.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 12 publications
(31 reference statements)
1
51
0
Order By: Relevance
“…The Alexander polynomials of a cube of resolutions (in Vassiliev's sense) of a singular knot were categorified in [1]. Moreover, a 1-variable extension of the Alexander polynomial for singular links was categorified in [11]. The generalized cube of resolutions (containing Vassilievs resolutions as well as those smoothings at double points which preserve the orientation) was categorified in [12].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…The Alexander polynomials of a cube of resolutions (in Vassiliev's sense) of a singular knot were categorified in [1]. Moreover, a 1-variable extension of the Alexander polynomial for singular links was categorified in [11]. The generalized cube of resolutions (containing Vassilievs resolutions as well as those smoothings at double points which preserve the orientation) was categorified in [12].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Remark 6.8. It is interesting to compare the 'figure-8' curve to the local Heegaard diagram for a singular crossing in [23], as the number of generators agree for the second loop, up to an additional tensor factor. Also note that the proposition above gives rise to an exact triangle similar to the one in [30].…”
Section: Skein Exact Sequencesmentioning
confidence: 99%
“…The knot Floer edge ring is defined over Z[t −1 , t]], the ring of Laurent series in t, while the HOMFLY-PT edge ring is defined over Q [8,13] or Z [9]. The variable t appears in the definition of the knot Floer ideals as well because the knot Floer graph homology is in fact the singular knot Floer homology [11] of the graph in S 3 , computed with a particular choice of twisted coefficients. (2) The non-local ideal.…”
Section: • •mentioning
confidence: 99%
“…Ozsváth and Szabó constructed the original cube of resolutions for knot Floer homology from the collection of B(G e I ) for I ∈ {0, 1} n , which arose for them as singular knot Floer homology [11] with twisted coefficients. They showed that their cube of resolutions complex is the E 1 page of a spectral sequence to HF K − (K) that collapses at the E 2 page [12, Theorem 1.1, Section 5].…”
Section: If That Conjecture Holds It Would Follow Immediately That Bmentioning
confidence: 99%